2003
DOI: 10.1007/s00415-003-1009-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients with psychogenic nonepileptic seizures, alone or epilepsy-associated, share a psychological profile distinct from that of epilepsy patients

Abstract: The aim of this study was twofold: 1 - to identify a psychological profile of patients with psychogenic nonepileptic seizures (PNESs) that is possibly distinct from that of subjects affected by epileptic seizures (ESs) alone; 2 - to detect the possible differences between the clinical features and psychological profile of patients affected by PNESs alone and those of subjects in whom PNESs are associated with epileptic seizures (ES/PNES patients). We assessed the psychological profiles of 2 different groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(87 citation statements)
references
References 30 publications
10
74
3
Order By: Relevance
“…Desynchronization of information integration circuits leads to an emotion regulation and executive control failure where PFC and other related areas are unable to stop the underlying limbic avalanche (Lanius et al, 2014b). In this context, high emotional reactivity arises, consistent with well-known clinical features and personality manifestations in conversion patients suffering from pseudoseizures (Galimberti et al, 2003;Almis et al, 2013).…”
Section: Pseudoseizuressupporting
confidence: 67%
“…Desynchronization of information integration circuits leads to an emotion regulation and executive control failure where PFC and other related areas are unable to stop the underlying limbic avalanche (Lanius et al, 2014b). In this context, high emotional reactivity arises, consistent with well-known clinical features and personality manifestations in conversion patients suffering from pseudoseizures (Galimberti et al, 2003;Almis et al, 2013).…”
Section: Pseudoseizuressupporting
confidence: 67%
“…Studies comparing anxiety in individuals with PNESs and epilepsy have failed to identify clear and consistent differences, although the prevalence rates of anxiety disorders have been found to be approxi-mately twice as high in both groups as in the general population [25,26]. Some studies showed similar mean levels of self-reported anxiety in patients with epilepsy or PNESs [27,28], whereas others found significant [29] or trend-level differences [30].…”
Section: Anxiety and Avoidance In Psychogenic Nonepileptic Seizuresmentioning
confidence: 99%
“…Although previous studies have reported a high prevalence (5%-50%) of ES in PNES patients (PNES/ES) (Sigurdardottir and Olafsson, 1998;Benbadis et al, 2001;Martin et al, 2003), few authors investigated PNES and PNES/ES patients separately to determine the possible influence of this comorbidity on psychological and clinical aspects (Devinsky et al, 1996;Owczarek and Jederzejczak, 2001;Reuber et al, 2002;Kuyk et al, 2003;Galimberti et al, 2003).…”
mentioning
confidence: 99%